Pengaruh Promosi Media Sosial Tiktok, Electronic Word Of Mouth (E-Wom), dan Brand Image Terhadap Keputusan Pembelian Konsumen Klinik Pratama Rawat Jalan Da Skin Clinic Sragen - Almira Leta Sunarsasi; Pratiwi , Adcharina (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of TikTok social media promotion, electronic word of mouth, and brand image on consumer purchasing decisions at DA Skin Clinic Outpatient Clinic in Sragen. Data collection in this study used a questionnaires distributed online to respondents. The sample in this study amounted to 100 consumers of DA Skin Clinic Sragen, with the sampling technique using the Purposive Sampling technique. The analysis methods used in this study are descriptive anlysis, multiple linear regression analysis, t-test, F-test (model accuracy test) and determination coefficient test (R2). The results of the t-test of this study indicate that TikTok social media promotion has a significant effect on consumer purchasing decisions at the DA Skin Clinic Sragen Outpatient Clinic with a p-value = 0.000 <0.05, electronic word of mouth has a significant effect on consumer purchasing decisions at the DA Skin Clinic Sragen Outpatient Clinic with a p-value = 0.000 <0.05, and brand image has a significant effect on consumer purchasing decisions at the DA Skin Clinic Sragen Outpatient Clinic with a p-value = 0.000 <0.05.